Dualism in Indonesian Criminal Law: Between Codified Justice and Syariah Morality - Putra, Novaldi Abi; Saputri, Faradila Rizkia (Jurnal Ilmu Hukum Kyadiren, 2026)
This study is motivated by the dualism within Indonesia’s criminal law system, particularly between the 2023 Criminal Code (KUHP) as a form of national codification and the Aceh Qanun Jinayat as an embodiment of Islamic sharia-based autonomy. The purpose of this research is to analyze and compare the principles, objectives, types of sanctions, and sentencing mechanisms within these two systems, while identifying points of friction and forms of normative coexistence in relation to the principles of legality, proportionality, and the protection of human rights. A normative–comparative juridical approach was employed, involving the analysis of statutory provisions, legal doctrines, and judicial decisions. The findings reveal that the 2023 Criminal Code adopts a retributive–utilitarian–restorative balance, whereas the Qanun Jinayat emphasizes moral–religious legitimacy through hudud and ta’zir sanctions. It is concluded that harmonizing both systems requires an integrative framework grounded in legal pluralism that simultaneously ensures legal certainty and safeguards human rights.